Training on Silage Making for Farm Feed (Dairy Cows) with Forestry Plants Indigofera zollingeriana - Widia Sri Utami; Muhammad Rafii Nur Fauzan; Letus Sepsamli; Hengky Sipayung (Outline Publisher, 2025)
Farmers often have difficulty obtaining fresh forage feed to improve animal health and productivity. The problem of animal feed is one of the successes of farmers. Erratic seasonal changes cause difficulties in providing forage availability. One way to feed dairy cows is to utilize forestry plants, namely Indigofera zollingeriana, which is resistant to environmental conditions for growth and increase the growth of dairy cows with the practice of making probiotics and silage. Indigofera zollingeriana has better content for dairy cows than grass. The aim is to increase community knowledge and skills in managing animal feed in an independent and sustainable way. The method was to provide socialization and practice then evaluated with a questionnaire with 10 questions. There were 20 participants from one farmer group. The results of this activity are that the community understands very well the material and practice, which is an average of 84.38%. Participants were dominated by men as many as 15 people while the age range that dominated was age> 50 years as many as 11 people. The gender and age of participants affect the success of increasing the growth of dairy cows.